"If I Really Were a Witch": Narratives of Female Power in a Coastal Galician Community - Kelley, Heidi (Anthropologica, 2022)
In this paper, I call into question anthropological connotations of coastal Galician women's power as "absolute" and as based on the "matrifocal" family. My problematization of the main assumptions that underlie unambiguous theoretical assessments of women's power is drawn from the complexities and paradoxes revealed in five women's own accounts of the making of their casas, what I am calling their household narratives. The details and reflections contained in these narratives lead me to develop alternative conclusions about the relationship between kinship practice and gender politics in the coastal Galician village of Ezaro.